Research of physical and chemical characteristics of phospholipids’ water solution - Lazarenko, Tatiana; Mank, Valeriy (My University, 2012)
The electrokinetic potential\potential of phospholipids was determined during the research. Adsorption isotherm of phospholipids that in the surface layer and the possible size of the molecules of phospholipids in the interfacial environment were determined. Впродовж дослідження був визначений електрокінетичний потенційний\дзета-потенціал фосфоліпідів. Були визначені адсорбційна ізотерма фосфоліпідів, що знаходяться в зовнішньому шарі і можливий розмір молекул фосфоліпідів.
Keywords: phospholipids; фосфоліпіди; фосфолипиды; electrophoretic phospholipids mobility; potential; електрофоретична рухливість фосфоліпідів; потенціал; электрофоретическая подвижность фосфолипидов; потенциал; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів